Considerations on the Patriarcha - Shervin Moghimi Zanjani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The main subject of this paper is Robert Filmer’s Patriarcha which is the essential text in the history of political thought and in a sense it is one of the most important sources of the controversial debates on politics in early modern England. We think that Patriarcha was one of the last systematic and coherent attempts to defend the "natural character of politics" and "divine right of kings to rule given by God alone. We try to show that Filmer’s point of view, in spite of its affinities with ancient political philosophers, it was essentially different because it is totally based on the revelation. Generally, we will attempt to understand Filmer’s text in the light of the rhetorical war between the defenders of the pre-modern political conception (emphasizing the naturalness of politics and denying the equity in political rights)  and the proponents of the new politics (emphasizing the artificial character of politics and the idea of ‘the individual possessed unconditional right by nature”.) Also, we cast light on the Persian translation of the Patriarcha and argue that the non-literalness of this rendering has led to some misunderstandings and erroneous equivalents.